Adaptasi Komunitas Adat Terpencil di Kepulauan Mentawai dan Pulau Rupat terhadap Regulasi Keagamaan Nasional - Syahril Syahril; Ahmad Nurhuda; Suryadi Fajri; Ilhamdi Yusra; Aulia Rahmi Putri (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study examines two contrasting cases: the remote indigenous communities on Mentawai and Rupat Islands (Riau), where the majority of the original populations have formally adopted Christianity and Buddhism as their religious identities. The purpose of this research is to explore how indigenous belief systems are preserved amidst the pressures for religious conformity and to analyze the psychological preferences of remote indigenous communities when choosing one of the state-recognized religions. This study employs a case study design, focusing on remote indigenous communities in Rupat Kepulauan (the Akit people) and Mentawai Island (the Mentawai people). The findings reveal that remote indigenous communities in the Mentawai Islands are generally open to migrants, engage in cross-cultural communication, and experience social change through processes of acculturation, assimilation, and integration. Although a small segment continues to maintain ancestral beliefs exclusively, no discrimination is evident against them. Government efforts to integrate remote indigenous communities with mainstream society are conducted through persuasive empowerment strategies. The results highlight the importance of establishing formal legal recognition for the indigenous belief systems of remote communities.